Investigation of Pomegranate Seed Oil Effects on the Renal Function in Alloxan-induced Diabetic Male Rabbits - Ibrahim, Bushra R.; Khalil, Luma W.; Salih, Lina A. (Iraqi Journal of Science, 2021)
Diabetes is a chronic disease which has reached pandemic proportions in a lot of countries of the world. In spite of the remarkable development in therapeutics chemistry, the usage of customary drugs is still a common practice for the treatment of diabetes. The current study was designed to investigate the effects of pomegranate seed oil (PSO) on kidney functions in the experimentally-induced diabetes in male rabbits. Diabetes was experimentally introduced by the intraperitoneal injection of alloxan monohydrate (150mg/kg BW). After three days of alloxan injection, samples were taken for the determination of glucose concentration. Serum glucose concentration of 200mg/ml was considered as an indication of animal diabetes. The experimental part was begun after 7 days of alloxan injection. Thirty two adult male rabbits were arbitrarily separated into four groups and treated daily for 45 days. Group 1 was kept with no treatment, group 2 included animals treated with 30mg/kg BW PSO, group 3 included diabetic animals that received alloxan with a dose of 150mg/kg BW, and, finally, group 4 included animals that received alloxan (150mg/kg BW) and treated with PSO (30mg/kg BW). Fasting blood samples were collected by heart puncture technique after 45days of experiments to assess glucose levels.